Women struggles and large-scale diamond mining in Marange, Zimbabwe. Issue 4 (December 2015) - Muchadenyika, Davison
Abstract: The arrival of large-scale diamond mining activities brought hope and enthusiasm to many women within and around Marange, Mutare District, Zimbabwe. Ordinary Zimbabweans believed that diamond mining would transform the lives of the region's inhabitants. However, such anticipated transformation turned into rage and despair, and presented numerous challenges to residents, particularly women. This article examines the impacts mining activities have had on women in Eastern Zimbabwe, and explores their struggles.